Gross And Histomorphological Studies Of Sperm Storage Organ In Adult Indigenous Chicken (Gallus Domestics) Of Assam, India - Bharti , S.K.; Talukdar , S.R. (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
The present study was conducted on the gross and histomorphological structure of vagina (sperm storage organ) in indigenous chicken of Assam. Anterior part of the vagina forming a junction with uterus that is uterovaginal junction (UVJ) is referred as sperm storage tubule. The mucosa of vagina was lined by pseudostratified ciliated columnar epithelium with primary and secondary type folds and few goblet cells. The lamina propria-submucosa showed the presence of few tubular glands and it contained large amount of reticular fibres with scanty collagen and elastic fibres. Tunica muscularis consisted of thick inner circular and thin outer longitudinal layer. PAS positive reaction was intense in apical part of epithelium, moderate at central part of mucosal folds and lamina propria-submucosa was weak PAS positive.
Keywords: Chicken; Vagina; Gross; Histomorphology; Histochemistry